Symptom Burden and Palliative Referral Disparities in an Ambulatory South Texas Cancer Center - Cervantez, Sherri Rauenzahn; Tenner, Laura L.; Schmidt, Susanne; Aduba, Ifeoma O.; Jones, Jessica T.; Ali, Nazneen; Singh-Carlson, Savitri (Frontiers in Oncology, 2018)
Background: The American Society of Clinical Oncology’s recommendation for “dedicated palliative care services, early in the disease course, concurrent with active treatment” for cancer patients is a challenge for cancer centers to accommodate. Despite demonstrated benefits of concurrent care, disparities among socioeconomic and ethnic groups in access to supportive care services have been described. The aim of this project was to evaluate: a) how insurance coverage and ethnicity impact patient symptom burden and, b) how those factors influence palliative access for patients at a South Texas NCI-designated cancer center. Methods: During a 5-month retrospective period, 604 patients from five ambulatory oncology clinics completed the 10 question Edmonton Symptom Assessment Scale (ESAS) surveys during their clinic visit. Patient demographics, ESAS scores, palliative referral decisions, and time to palliative encounters were collected. We compared symptom burden and time to consult based on ethnicity and insurance status (insured = Group A; under-insured and safety net = Group B). Results: The mean ESAS score for all patients at the initial visit was 19.9 (SD=18.1). Safety net patients were significantly more likely to be Hispanic, younger in age, and have an underlying GI malignancy in comparison to insured patients; however, the symptom severity was similar between groups with over 40% of individuals reporting at least one severe symptom. Twenty-one referrals were made to palliative care. On average, Group B had 33.3 days longer wait times until their first potential visit (p<0.01) when compared to Group A. Time to actual visit was on average 57.6 days longer for patients in Group B compared to patients in Group A (p=0.01), averaging at 73.8 days for safety net patients. Conclusions: This project highlights the high symptom burden of oncology patients and disparities in access to services based on insurance coverage. This investigation revealed a 4-fold increase in the time to the first scheduled palliative care visit based on whether patients were insured versus under-insured. While this study is limited by a small sample size, data suggest that under-insured oncology patients may have significant barriers to palliative care services, which may influence their cancer care quality.